Brain Maturation, Cognition and Voice Pattern in a Gender Dysphoria Case under Pubertal Suppression - Schneider, Maiko A.; Spritzer, Poli M.; Soll, Bianca Machado Borba; Fontanari, Anna M. V.; Carneiro, Marina; Tovar-Moll, Fernanda; Costa, Angelo B.; da Silva, Dhiordan C.; Schwarz, Karine; Anes, Maurício; Tramontina, Silza; Lobato, Maria I. R. (Frontiers in Human Neuroscience, 2017)
Introduction: Gender dysphoria (GD) (DMS-5) is a condition marked by increasing psychological suffering that accompanies the incongruence between one's experienced or expressed gender and one's assigned gender. Manifestation of GD can be seen early on during childhood and adolescence. During this period, the development of undesirable sexual characteristics marks an acute suffering of being opposite to the sex of birth. Pubertal suppression with gonadotropin releasing hormone analogs (GnRHa) has been proposed for these individuals as a reversible treatment for postponing the pubertal development and attenuating psychological suffering. Recently, increased interest has been observed on the impact of this treatment on brain maturation, cognition and psychological performance. Objectives: The aim of this clinical report is to review the effects of puberty suppression on the brain during adolescence. White matter microstructure, voice and cognitive functions were assessed during 28 months of hormonal suppression. Methods: We performed a longitudinal evaluation of a pre-pubertal transsexual girl undergoing hormonal treatment with GnRH analog. Three longitudinal magnetic resonance imaging (MRI) scans were performed for diffusion tensor imaging (DTI). In parallel, voice samples for acoustic analysis as well as executive functioning with the Wechsler Intelligence Scale (WISC- IV) were performed. Results: During the follow-up, white matter fractional anisotropy did not increase, compared to normal male puberty effects on the brain. This result is a consequence of the lack of testosterone. After 22 months of pubertal suppression, operational memory dropped 9 points and remained stable after 28 months of follow-up. The fundamental frequency of voice varied during the first year; however, it remained in the female range. Conclusion: Brain white matter fractional anisotropy remained unchanged in the GD girl during pubertal suppression with GnRHa for 28 months, which may be related to the reduced serum testosterone levels. Global performance on the Weschler scale was slightly lower during pubertal suppression compared to baseline, predominantly due to a reduction in operational memory. Either a baseline of low average cognition or the hormonal status could play a role in cognitive performance during pubertal suppression. The voice pattern during the follow-up seemed to reflect testosterone levels under suppression by GnRHa treatment.